Immunopathogenesis of dengue virus and Salmonella typhi coinfection - Nugraheni, Enny; Sudiro, Tjahjani Mirawati; Nainggolan, Leonard; Fithriyah; Dewi, Beti Ernawati (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2024)
Typhoid, malaria, leptospirosis, dengue virus (DENV), and other arboviruses are endemic in Indonesia. Therefore, it is more likely that DENV and other infectious diseases could be coinfected. More severe symptoms, delayed identification, and ineffective treatment of the illness can all result from Salmonella typhi coinfection. To serve as a principle for clinicians’ considerations while diagnosing and prescribing, we aim to examine the immunopathogenesis of dengue associated with Salmonella typhi coinfection. Dengue virus has the potential to increase both susceptibility and incidence of this coinfection, leading to dengue haemorrhagic fever (DHF) with more severe clinical symptoms. This is explained by regulating impact of coinfection in the presence of gram-negative membrane endotoxin, DENV replication, and lipopolysaccharide (LPS). If Salmonella typhi coinfection is not treated promptly, both dengue and Salmonella typhi can affect several organs and result in significant morbidity and death. Dengue and typhoid immunopathogenesis coinfection are unclear. When dengue monoinfection compared with Salmonella dengue dual infections are related to higher fatality and morbidity rates.